Trial Characteristics That Affect Parental Consent in Neonatal Drug Trials - Hanvey, I. Blaire; Aliaga, Sofia; Laughon, Matthew M.; Testoni, Daniela; Smith, P. Brian; Bauserman, Melissa (American Journal of Perinatology, 2019)
Objective The main purpose of this article is to determine parental consent rates in neonatal drug trials and describe trial characteristics associated with higher rates.Study Design We included neonatal drug trials published between 2009 and 2014 and compared parental consent rates among the following characteristics: phase type, gestational age, randomization type, drug administration route, drug dosing frequency, blood sampling, control type, length of study, funding source, and length of treatment. We compared characteristics using chi-square, Fisher's exact, one-way analysis of variance or Kruskal–Wallis tests.Results We identified 52 trials: 38 trials (73%) reported data of parental consent. Median percentage (interquartile range) of parental consent was 79% (62, 89). Higher rates were observed in studies that used active comparators (87%) and shorter study lengths (81% for studies <24 hours).Conclusion Parental consent rates for neonatal drug trials varied by study characteristics. Information on proportion of parents consented is valuable to assess generalizability of trial results and for preparing trial protocols.
Keywords: newborn; clinical trial; parental consent; informed consent